2005
DOI: 10.1016/j.adolescence.2005.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Future expectations of Brasilian street youth

Abstract: Future expectations of youth surviving on the streets of Porto Alegre, Brasil, were examined. The sample consisted of 35 boys and 34 girls aged 10-18 (M age 14.4) who participated in a sentence completion task and semi-structured interviews. Responses to two incomplete sentences regarding the future revealed a mismatch between hoped-for and expected events. When completing the sentence, "In the future, I hope…" the majority of youth gave optimistic (but generally non-specific) responses. In contrast, the sente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 34 publications
1
25
0
5
Order By: Relevance
“…Little respect is given to those with limited street smarts or those who remain connected to traditional sources of support, demonstrating these youths' conviction concerning the significance of independence and its role in homelessness. Gaining experience on the street significantly shapes these young people's behaviors and perceptions (Raffaelli & Koller, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Little respect is given to those with limited street smarts or those who remain connected to traditional sources of support, demonstrating these youths' conviction concerning the significance of independence and its role in homelessness. Gaining experience on the street significantly shapes these young people's behaviors and perceptions (Raffaelli & Koller, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study in Brazil too, concluded the same. 11 Other studies report 69-79% substance use. 12,13 The higher incidence in these studies was seen probably because these were conducted among street children who were regularly exposed to street conditions including substance use.…”
Section: Future Aspiration Of the Childrenmentioning
confidence: 97%
“…Casual, unskilled employment often does not provide enough income for street youth to afford stable accommodation. 16,20 Limited education, a lack of marketable job skills and the generalized emotional and cognitive instability associated with homelessness itself contribute to these youth's dependency on the "street economy" (e.g. sex trade, panhandling, drug running) as their primary source of income to meet their basic needs for food, clothing and shelter.…”
Section: Canadian Street Youth: a Vulnerable Populationmentioning
confidence: 99%